Universal Nonadiabatic Control of Small-Gap Superconducting Qubits - Daniel L. Campbell; Yun-Pil Shim; Bharath Kannan; Roni Winik; David K. Kim; Alexander Melville; Bethany M. Niedzielski; Jonilyn L. Yoder; Charles Tahan; Simon Gustavsson; William D. Oliver (Physical Review X, 2020)
Resonant transverse driving of a two-level system as viewed in the rotating frame couples two degenerate states at the Rabi frequency, an equivalence that emerges in quantum mechanics. While successful at controlling natural and artificial quantum systems, certain limitations may arise (e.g., the achievable gate speed) due to nonidealities like the counterrotating term. We introduce a superconducting composite qubit (CQB), formed from two capacitively coupled transmon qubits, which features a small avoided crossing—smaller than the environmental temperature—between two energy levels. We control this low-frequency CQB using solely baseband pulses, nonadiabatic transitions, and coherent Landau-Zener interference to achieve fast, high-fidelity, single-qubit operations with Clifford fidelities exceeding 99.7%. We also perform coupled qubit operations between two low-frequency CQBs. This work demonstrates that universal nonadiabatic control of low-frequency qubits is feasible using solely baseband pulses.